Chapter Il linguaggio della scienza e la creazione della terminologia - Villa, Maria Luisa (Proceedings e report, 2021)
This paper aims to present an historical point of view and precisely exposes the reasons why the need for terminology has developed and gradually increased, without it nullifying the ability of scientists to invent words with freedom and imagination, sometimes even taking inspiration from literature, such as particle physicist Murray Gell-Mann (Nobel laureate 1969), who, for "quark", was inspired by a passage from Joyce's Finnegans Wake.